The Existence of Bujang Kurap Folklore as Social Capital in Lubuklinggau - Ismawati, Dwi; Puspita, Yenda; Sari, Dwi Lyna (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the existence of the Bujang Kurap folklore in Lubuklinggau. Data collection techniques used in this study were questionnaires and interviews. Respondents in the study were 60 respondents, which were divided into junior high school students, senior high school students, and university students. Based on the results of the study, it was found that 68.23% of students did not know the Bujang Kurap folk story, with details of data on 31.50% of junior high school students in the poor category, 43.2% in high school students in the sufficient category, and in students, the percentage obtained was 33.73% in the category not good. The people of Lubuklinggau, South Sumatra have quite diverse folklore. The Bujang Kurap folklore no longer exists among the wider community, this can be seen from the lack of public appreciation for folklore, which is supported by survey results, only 35% know about Bujang Kurap folklore. Lubuklinggau folklore even though it contains many values of moral education. The younger generation in Lubuklinggau prefers modern shows, causing traditional cultural treasures to be alienated and marginalized and folklore is no longer one of the media used by families in instilling moral values and forming children's moral behavior from an early age.